Spatial Distributions of Single-Molecule Reactivity in Plasmonic Catalysis - Ezendam, Simone (2024)
Plasmonic catalysts have the potential to accelerate and control chemical reactions with light by exploiting localized surface plasmon resonances. However, the mechanisms governing plasmonic catalysis are not simple to decouple. Several plasmon-derived phenomena, such as electromagnetic field enhancements, temperature, or the generation of charge carriers, can affect the reactivity of the system. These effects are convoluted with the inherent (nonplasmonic) catalytic properties of the metal surface. Disentangling these coexisting effects is challenging but is the key to rationally controlling reaction pathways and enhancing reaction rates. This study utilizes super-resolution fluorescence microscopy to examine the mechanisms of plasmonic catalysis at the single-particle level. The reduction reaction of resazurin to resorufin in the presence of Au nanorods coated with a porous silica shell is investigated in situ. This allows the determination of reaction rates with a single-molecule sensitivity and subparticle resolution. By variation of the irradiation wavelength, it is possible to examine two different regimes: photoexcitation of the reactant molecules and photoexcitation of the nanoparticle’s plasmon resonance. In addition, the measured spatial distribution of reactivity allows differentiation between superficial and far-field effects. Our results indicate that the reduction of resazurin can occur through more than one reaction pathway, being most efficient when the reactant is photoexcited and is in contact with the Au surface. In addition, it was found that the spatial distribution of enhancements varies, depending on the underlying mechanism. These findings contribute to the fundamental understanding of plasmonic catalysis and the rational design of future plasmonic nanocatalysts.